Emancipación y guerra en el Río de la Plata, 1840-1865: hacia una historia social de las relaciones internacionales - Grinberg, Keila (El Colegio de México, A.C., 2019)
The causes of the Paraguay War or the War of the Triple Alliance (1864-1870) have been debated ever since its conclusion and remain controversial among historians to this day. This article analyzes the relationship between the Brazilian political situation and the process of abolishing slavery in Uruguay between the 1840s and 1860s, arguing that the presence of Brazilian slaves and slaveowners in Uruguay affected the international relations of the countries of the Río de la Plata region in the 19th Century, making an essential contribution to the tensions that led to the outbreak of war. Beyond this argument, by using documents and methods typical of traditional political history and social history, it also defends the relevance of the study of international relations through a social history perspective by showing that cross-border migratory phenomena involving runaway slaves, the violence of military and militia recruitment in Uruguay and Brazil and attacks on communities of freedmen had an important international dimension that must be understood in order to comprehend the origins of the Paraguay War.